Psychological antecedents and psychological benefits of physical exercise for the elderly under the elderly law - Jian Liu; Xuemin Deng, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The study investigates the psychological antecedents and advantages of physical exercise for the old under the law governing the aged. This paper studies the effects of physical exercise on psychological emotion and psychological benefits by employing a questionnaire and referring to the law of older people. The study discovered that the psychological advantages of physical exercise for the elderly depend on the amount of exercise performed each week and the time spent exercising. Individuals who exercise more than five times per week and for at least 30 minutes are more mentally healthy. Physical exercise can not only improve mood, enhance self-concept and coordinate interpersonal relations, but also eliminate fatigue, reduce stress response, reduce or eliminate mental diseases to indeed promote the fitness and mental health of the elderly.